Komunikasi Pemasaran Studio Lunanuova dalam Membangun Brand Awareness - Pudrianisa, Sheila Lestari Giza; Ali Topan, Mohammad (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
Competition among business actors in the business world is increasing, so that appropriate strategies are needed in introducing and promoting a product. The goal is that the products offered are not drowned by the many competitors. Lunanuova's study is one of the companies trying various strategies to build an image as the face of the company. So the research focuses on seeing how Studio Lunanuova's marketing communications build brand awareness. The theory used is in the form of marketing communications (7P) and brand awareness with a qualitative descriptive method and post positivism paradigm. The researcher interviewed 3 informants using a purposive sampling technique so that they met the criteria according to the focus of the problem. The research resulted in the 6 most effective marketing communication mixes in the form of products because they have the advantage of always offering different products every year and all files without additional costs. Prices are much cheaper according to the lower middle segment and there are special prices for card members. Promotion in the form of product bundling, price discounts, and give away to establish interaction with customers. At the process stage and people are connected to each other because Studio Lunanuova has an SOP for employees, especially hospitality so that the activities carried out go according to the wishes of the customer. Placing various product photos in every corner of the room to convince consumers that Lunanuova Studio's work is a mix of physical evidence. The mix that is not very effective is in the form of place because the location is too far from the city center. The marketing communication mix that has been implemented has made Lunanuova Studio better known to customers with a positive image.